Standardization of Fruit of Tribulus terrestris Linn. - Gupta, S.K.; Sharma, P.K.; Ansari, S.H. (Asian Journal of Chemistry, 2016)
Different parts of Tribulus terrestris Linn. are highly prized remedy amongst the people of India. Since ancient period the fruit is used as demulcent, diuretic, antispasmodic and aphrodisiac. Fruits have been identified by their macroscopic and microscopic characters, cell contents, behaviour of powdered drug with different re-agents and preliminary phytochemical analysis.